The Governance of Agrobiodiversity - Visser, Bert; Brush, Stephen B.; Aistara, Guntra A.; Andersen, Regine; Jäger, Matthias; Nemogá, Gabriel; Padmanabhan, Martina; Sherwood, Stephen G. (MIT Press, 2019)
Agrobiodiversity relates to humans and their environments. It is the result of interactions between humans and nature, and thus is simultaneously social and biological by nature. Without humans, agrobiodiversity would not exist. Seeds, as carriers of major agrobiodiversity components, are not mere material objects that exist outside of social relations: they are also sociobiological artifacts embedded in these relations. The multifaceted, highly dynamic realities of agrobiodiversity mean that those interested in questions of governance need to understand the limitations and political implications of the complementary and sometimes contradictory instrumental and relational perspectives on seeds; that is, the understanding of seeds as a production input or as the subject of a social network, in which agrobiodiversity brings together production and social linkages. International instruments aim to provide a legal basis for mediating competing interests and methodologies. In addressing governance, the global framing of these instruments refl ects the dynamics of agrobiodiversity in global socioeconomic and environmental changes. From the earliest recognition of the potential value of crop diversity, crop genetic resources were treated as public goods in the public domain. Breeding companies have opposed this treatment. Breeders sought exclusivity and reward for their creative activities in using genetic resources to create novel varieties. Governance of agrobiodiversity—defi ned by a set of relationships that infl uences the access to and conservation, exchange, and commercialization of agrobiodiversity—refl ects underlying value systems. Confl icting approaches (e.g., “stewardship” vs. “ownership” approaches) toward governance based on divergent value systems and rationales can be distinguished. It is important to identify the actors involved, from local to global, to understand the power dynamics that infl uence the interactions among these various actors and their ability to infl uence or control the management of agrobiodiversity. The governance of agrobiodiversity and the power dynamics involved are increasingly crucial in the context of rapidly changing farming and food systems, especially in the context of globalization, migration, and urbanization. This chapter elaborates an emergent research agenda, focusing on aspects of power relations in agrobiodiversity governance, agrobiodiversity and food systems, nutrition, taste and health, and the governance of genetic information.